Cartel pricing dynamics with cost variability and endogenous buyer detection - Joseph E. Harrington; Joe Chen (The Johns Hopkins University, Department of Economics, 2004)
This paper characterizes collusive pricing patterns when buyers may detect the presence of a cartel. Buyers are assumed to become suspicious when observed prices are anomalous. We find that the cartel price path is comprised of two phases. During the transitional phase, price is generally rising and relatively unresponsive to cost shocks. During the stationary phase, price responds to cost but is much less sensitive than under non-collusion or simple monopoly. The length of the transition phase is decreasing in the variance of cost shocks. It is also shown that the cartel price path may overshoot its long-run level so that price converges from above.
Keywords: 330; Kartell; Preisabsprache; Theorie